Evaluation of zinc oxide nanoparticles on lettuce (Lactuca sativa L.) growth and soil bacterial community - Xu, Jiangbing; Luo, Xiaosan; Wang, Yanling; Feng, Youzhi (Environmental science and pollution research international, 2018)
The wide spread of nanoparticles (NPs) has caused tremendous concerns on agricultural ecosystem. Some metallic NPs, such as zinc oxide (ZnO), can be utilized as a nano-fertilizer when used at optimal doses. However, little is known about the responses of plant development and concomitant soil bacteria community to ZnO NPs. The present pot experiment studied the impacts of different doses of ZnO NPs and bulk ZnO (0, 1, 10, 100 mg ZnO/kg), on the growth of lettuce ( Lactuca sativa L.) and the associated rhizospheric soil bacterial community. Results showed that at a dose of 10 mg/kg, ZnO NPs and bulk ZnO, enhanced the lettuce biomass and the net photosynthetic rate; whereas, the Zn content in plant tissue was higher in NPs treatment than in their bulk counterpart at 10 mg/kg dose or higher. For the underground observations, 10 mg/kg treatment doses (NPs or bulk) significantly changed the soil bacterial community structure, despite the non-significant variations in alpha diversity. Taxonomic distribution revealed that some lineages within Cyanobacteria and other phyla individually demonstrated similar or different responses to ZnO NPs and bulk ZnO. Moreover, some lineages associated with plant growth promotion were also influenced to different extents by ZnO NPs and bulk ZnO, suggesting the distinct microbial processes occurring in soil. Collectively, this study expanded our understanding of the influence of ZnO NPs on plant performance and the associated soil microorganisms.